Maternal characteristics and causes associated with refractory postpartum haemorrhage after vaginal birth: a secondary analysis of the WHO CHAMPION trial data. (8th January 2020) - Widmer, M; Piaggio, G; Hofmeyr, GJ; Carroli, G; Coomarasamy, A; Gallos, I; Goudar, S; Gülmezoglu, AM; Lin, SL; Lumbiganon, P; Mugerwa, K; Owa, O; et al.
Abstract : Objective: To assess the maternal characteristics and causes associated with refractory postpartum haemorrhage (PPH). Design: Secondary analysis of the WHO CHAMPION trial data. Setting: Twenty‐three hospitals in ten countries. Population: Women from the CHAMPION trial who received uterotonics as first‐line treatment of PPH. Methods: We assessed the association between sociodemographic, pregnancy and childbirth factors and refractory PPH, and compared the causes of PPH between women with refractory PPH and women responsive to first‐line PPH treatment. Main outcome measures: Maternal characteristics; causes of PPH. Results: Women with labour induced or augmented with uterotonics (adjusted odds ratio [aOR] 1.35; 95% CI 1.07–1.72), with episiotomy or tears requiring suturing (aOR 1.82; 95% CI 1.34–2.48) and who had babies with birthweights ≥3500 g (aOR 1.33; 95% CI 1.04–1.69) showed significantly higher odds of refractory PPH compared with the reference categories in the multivariate analysis adjusted by centre and trial arm. While atony was the sole PPH cause in 53.2% (116/218) of the women in the responsive PPH group, it accounted for only 31.5% (45/143) of the causes in the refractory PPH group. Conversely, tears were the sole cause in 12.8% (28/218) and 28% (40/143) of the responsive PPH and refractory PPH groups, respectively. Placental problems were the sole cause in 11 and 5.6% in the responsive and refractory PPH groups, respectively. Conclusion: Women with refractory PPH showed a different pattern of maternal characteristics and PPH causes compared with those with first‐line treatment responsive PPH. Tweetable abstract: Women with refractory postpartum haemorrhage are different from those with first‐line treatment responsive PPH. Tweetable abstract: Women with refractory postpartum haemorrhage are different from those with first‐line treatment responsive PPH.